2019
DOI: 10.1080/21623945.2019.1701387
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between epicardial adipose tissue thickness and epicardial adipocyte size with increasing body mass index

Abstract: Macroscopic deposition of epicardial adipose tissue (EAT) has been strongly associated with numerous indices of obesity and cardiovascular disease risk. In contrast, the morphology of EAT adipocytes has rarely been investigated. We aimed to determine whether obesity-driven adipocyte hypertrophy, which is characteristic of other visceral fat depots, is found within EAT adipocytes. EAT samples were collected from cardiac surgery patients (n = 49), stained with haematoxylin & eosin, and analysed for mean adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 43 publications
4
30
0
2
Order By: Relevance
“…However, other studies have failed finding correlation between adipocyte size and visceral mass expansion, as in the case of epicardial thickness. This may be due to the heterogeneity of adipocytes size in VAT from different body sites, or dissimilarities regarding BMI and gender distribution between study populations 20 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have failed finding correlation between adipocyte size and visceral mass expansion, as in the case of epicardial thickness. This may be due to the heterogeneity of adipocytes size in VAT from different body sites, or dissimilarities regarding BMI and gender distribution between study populations 20 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small number of subjects, we demonstrated that EAT volume has a positive correlation with BMI, confirming the association observed in previous studies. 42,43 For a long time, the research has been focused on the role of abdominal visceral adipose tissue in cardiovascular diseases. However, due to contiguity with coronary arteries, the EAT could be decisive in the onset, progression, and calcification of atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EAT may be a potential therapeutic target in cardiovascular disease, and it is necessary to determine the size and the adiposopathy grade of EAT as a risk factor of CAD. 42 In addition, it should be considered that the anatomical location of EAT is related with its secretor pattern. 44 This suggests that not only the EAT per se, but also its anatomical localization is crucial in the artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Aitken-Buck et al 59 has suggested that the expansion of EAT is different from that of the visceral and subcutaneous adipose tissue. It has previously been reported that the primary mechanism of fat depot expansion for visceral and subcutaneous adipose tissue is dependent on adipocyte hypertrophy, but that is not the case with EAT.…”
Section: Relation To Other Fat Depotsmentioning
confidence: 98%
“…Conversely, the authors suggests hyperplasia to be the primary remodelling mechanism for EAT, but it remains unclear to what extent the physiology and metabolic functions of EAT are affected by this. 59 It is, therefore, expected that visceral, subcutaneous and epicardial fat depots will respond differently to lifestyle or pharmaceutical interventions and a future investigation to explain these differences are warranted.…”
Section: Relation To Other Fat Depotsmentioning
confidence: 99%